Evaluation of lacrimal system outflow in the newborn by dye tests - Schellini, Silvana Artioli [UNESP]; Hoyama, E. [UNESP]; Rocha, M. C. [UNESP]; Rugollo A., Jr [UNESP]; Padovani, Carlos Roberto [UNESP] (Swets & Zeitlinger Publishers, 2000)
PURPOSE: The aim of this study was to evaluate the outflow from the lacrimal excretory system (LES) at birth. METHOD: Two-hundred LES were evaluated by the Milder Test (DDT) and the modified Jones I Test (JIT) in 100 newborns (NBs) from 31 (T 1) until 42 (T 3) weeks of gestational age. The occurrence of obstruction was related to sex, weight at birth, presence of ocular discharge and the degree of maturity. RESULTS: Both tests were in agreement and showed LES obstruction in 61.5% (DDT) and 78.5% (JIT), respectively, while the LES outflow increased with increasing maturity. CONCLUSION: Evaluation of LES outflow at birth reveals obstruction rates that are much higher than those clinically observed in children with complaints of epiphora.
Keywords: Epiphora; Gestational age; Jones I Test; Lacrimal excretory system obstruction; Milder Test; Newborn; birth weight; controlled study; epiphora; evaluation; female; fetus maturity; human; Jones I test; lacrimal duct occlusion; major clinical study; male; Milder test; newborn; sex difference; staining; tear flow; technique